Did the Fed and ECB react asymmetrically with respect to asset market developments? - Andreas Hoffmann (Universität Leipzig, Wirtschaftswissenschaftliche Fakultät, 2012)
This paper studies the monetary policy of the Federal Reserve (Fed) and the Bundesbank / European Central Bank (ECB) with respect to stock or/and foreign exchange markets from 1979 to 2009. I find that Fed policy changed over time, dependent on the chairman of the Fed. During the Greenspan era stock markets mattered for the Fed. In this period, the Fed lowered interest rates when stock prices fell, but did not raise interest rates in the boom. This asymmetry potentially put a downward pressure on interest rates. For the ECB, the exchange rate to the dollar played a role in monetary policy decisions until 2006. While I do not find evidence of asymmetric monetary policy with respect to the stock market, the ECB may be argued to indirectly have followed asymmetric US monetary policy via the exchange rate channel.
Keywords: E52; E61; 330; monetary policy; Taylor rule; asset prices; Geldpolitik; Taylor-Regel; Börsenkurs; Aktienmarkt; Wechselkurs; Devisenmarkt; USA; Deutschland; Eurozone